Zasadność stosowania strategii relacyjnej w małych przedsiębiorstwach - Bąkowska-Morawska, Urszula (Legitimacy of Applying the Relations Strategy in Small Enterprises, 2006)
The traditional methods of management in small enterprises functioning in more and more turbulent surroundings not always turn out to be good. One of new methods of management used in small enterprises is the relations strategy which is based on logging and utilization of the connections. The basis of identification of the relations strategy, being an element of general strategy of a firm are "formal matrices" proposed by authoress.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 411-418